Kontribusi Implementasi Asesmen Diagnostik dan Formatif terhadap Kualitas Pembelajaran Anak Usia Dini di TK Al-Hikmah - Muslimaeni; I Wayan Karta; Filsa Era Sativa (Mataram University, 2026)
This study aims to determine the contribution of diagnostic assessment and formative assessment to the quality of early childhood learning. Based on the conditions at TK Al-Hikmah, diagnostic and formative assessments have not been implemented consistently and systematically in the learning process. Previous studies have mostly discussed the two types of assessment separately, so there is still limited research examining their simultaneous contribution to the quality of early childhood learning. This study employed an ex post facto approach with a quantitative method and correlational technique. The research subjects were early childhood learners, while the data collection technique was carried out using questionnaires. Data analysis used descriptive and inferential statistics through multiple linear regression. The results showed that diagnostic assessment and formative assessment simultaneously contributed significantly to the quality of early childhood learning. This indicates that the integrated implementation of both types of assessment can support the improvement of learning quality more optimally. In addition, partially, diagnostic assessment made a significant contribution to the quality of early childhood learning, meaning that the better the implementation of diagnostic assessment, the higher the quality of learning. Formative assessment also made a significant contribution to the quality of early childhood learning, indicating that the proper implementation of formative assessment can support a more effective learning process. Thus, it can be concluded that diagnostic assessment and formative assessment play an important role in improving the quality of early childhood learning, both simultaneously and partially. Therefore, educators are encouraged to improve their competence in designing and implementing diagnostic and formative assessments through training and professional development to support the improvement of the quality of early childhood learning.